Modeling Studi Of Flexural Pavement on Soft Soil Using Plaxis 2d Software - Rumbyarso, Yonas Prima Arga; Pratikso, P; Arief, Rifqi Brilyant (Universitas Islam Sultan Agung, 2025)
Road construction on soft soils presents significant technical challenges due to the natural properties of the soil such as low bearing capacity, high compressibility and limited shear strength. This study aims to analyze the response of soft clay soil to vertical loads under varying water infiltration conditions using numerical modeling with PLAXIS 2D software. Modeling was performed at a laboratory scale of 1:20 with a soft soil thickness of 57 cm and a 3 cm thick flexible pavement layer. Simulations were conducted under three water addition scenarios: 19%, 36%, and 53%, each with a waiting period of 3 days before a load of 20.4 kg was applied. The simulation results showed that increasing the water content significantly affected the soil deformation (displacement), with vertical settlement values of 0.06128 mm, 0.1342 mm, and 1.039 mm for the 19%, 36%, and 53% scenarios, respectively. Meanwhile, the effective stress values also experienced a limited increase, namely 10.17 kN/m², 11.39 kN/m², and 11.41 kN/m². This finding indicates that although the effective stress increases numerically, saturated conditions due to high infiltration can actually decrease the overall stability of the soil.